Alternating electric field stimulation: Phenotype analysis and osteoclast activity of differentiated RAW 264.7 macrophages on hydroxyapatite-coated Ti6Al4V surfaces and their crosstalk with MC3T3-E1 pre-osteoblasts - Kreller, Thomas; Zimmermann, J.; van Rienen, U.; Boccaccini, Aldo R.; Jonitz-Heincke, A.; Detsch, Rainer (Biomaterials Advances, 2023)
Biophysical stimuli can mimic endogenous electric potentials and currents in the natural bone to enhance tissue healing and reconstruction in diseased bone. However, little is known about the influence of electric fields on osteoclasts. Therefore, this study aimed to investigate the effects of alternating electric fields on osteoclast differentiation and activity. In this in vitro study, RAW 264.7 cells were seeded on Ti6Al4V substrates, as a loadbearing implant material modified with biomimetic calcium phosphate (BCP) and stimulated towards osteoclastic differentiation via growth factors. The effects of directly coupled alternating electric fields (0.7 Vrms, 20 Hz) on cell behavior were examined for up to 28 days. Alternating electric field simulation was performed using the finite element method. Changes in cell and substrate morphology were examined via light and fluorescence imaging. Cell viability was assessed via WST-8 assay. The effect of electrical stimulation (ES) on intercellular signaling and crosstalk was evaluated using indirect co-cultures with murine MC3T3-E1 pre-osteoblasts by qPCR. Morphological analysis proved the successful differentiation of macrophages into osteoclast-like cells for both electrically stimulated samples as well as unstimulated controls. ES promoted RAW 264.7 viability within the first seven days and induced a cellular response at gene expression levels. Gradually decreased expression rates of genes related to osteoclast differentiation and activity within 28 days could indicate a long-term inhibitory effect of ES on osteoclastogenesis and osteoclast activity while significantly upregulated carbonic anhydrase type 2 expressions could be a consequence of membrane depolarization to maintain intercellular pH levels. In this context, we were also able to demonstrate the degradation of the BCP surface by cellular influence. ES affected the crosstalk between osteoblast-, and osteoclast-like cells. Supernatants of electrically stimulated RAW 264.7 specimens led to decreased MC3T3-E1 viabilities and mineralization. While osteopontin expression in MC3T3-E1 cells was significantly decreased, markers of osteogenic differentiation showed higher expression rates. Underlying biophysical mechanisms in combination with biomaterials are part of ongoing research.
CRIS-Team Scopus Importer:2023-01-20
Keywords: Alternating electric fields; Electrical stimulation; Hydroxyapatite; Osteoclasts; RAW 264.7